2015
DOI: 10.3748/wjg.v21.i4.1284
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status and viral response to therapy in hepatitis C infected children

Abstract: Adding vitamin D to conventional Peg/RBV therapy significantly improved the virological response and helped to prevent the risk of emerging bone fragility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 33 publications
2
19
0
2
Order By: Relevance
“…Similar to this result, the reported mean of vitamin D by [19] of HBV patients were lower than the reported mean of vitamin D by [20] of HCV patients, both in Egypt.…”
Section: Levels Of Calcitriol (Vitamin D3) (Pmol/l) In Studied Groupssupporting
confidence: 81%
“…Similar to this result, the reported mean of vitamin D by [19] of HBV patients were lower than the reported mean of vitamin D by [20] of HCV patients, both in Egypt.…”
Section: Levels Of Calcitriol (Vitamin D3) (Pmol/l) In Studied Groupssupporting
confidence: 81%
“…The results presented here indicate that 24 weeks of 250 cc of CM twice a day with Peg IFN/RBV achieved EVR12, ETR 24 , and SVR 24 of 60%, 90%, and 100%. Peg IFN/RBV achieved EVR 12 , ETR 24 , and SVR 24 of 15%, 70%, and 71%.…”
Section: Discussionmentioning
confidence: 60%
“…Results of a study conducted on 31 patients to investigate the role of vitamin D, suggested that the intake of 2000 units of vitamin per day, significantly decreased AST enzyme and viral load. According to this study, deficiency of vitamin D ef- fects the response to treatment; therefore, vitamin D supplementation could contribute to better responses (24). Vitamin content of camel milk could play a role in response improvement.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations